Parental knowledge of oral and dental health maintenance and caries in children with down syndrome relationships in Universitas Airlangga Dental Hospital - Zumaroh, Oktiana; Hidayati, Sri; Ulfah, Siti Fitria (Indonesian Journal of Dental Medicine, 2025)
Background: Down syndrome is a genetic disorder caused by trisomy of chromosome 21. Individuals with Down syndrome have immunological deficiencies that increase their susceptibility to oral infections, including dental caries. One important factor affecting the prevalence of dental caries in children with Down syndrome is parental understanding. Purpose: This study aims to examine the relationship between parental knowledge of oral health maintenance and the incidence of dental caries in children with Down syndrome visiting the Dental and Oral Hospital of Universitas Airlangga in 2025. Methods: A cross-sectional study was conducted involving 30 parents of children with Down syndrome attending Dental and Oral Hospital of Universitas Airlangga. Data were collected using a questionnaire to assess parental knowledge and a DMF-T index to evaluate the children's dental caries status. The relationship between dental caries incidence and parental knowledge was examined using the Spearman rank correlation test. Results: Up to 21 parents or guardians (70%) exhibited a deficient degree of understanding, and 10 children (33.3%) exhibited significantly elevated DMF-T scores. The Spearman rank test indicated a significant correlation (p = 0.023), indicating that there was a relationship between parents’ knowledge of oral health care and dental caries in kids with Down syndrome visiting Dental and Oral Hospital of Universitas Airlangga. Conclusion: Dental cavities in children with Down syndrome are inversely correlated with parental or guardian knowledge; the higher the caries rate, the lower the knowledge.